Factors Affecting Tax Avoidance In Property And Real Estate Sub Sector Companies Listed On The Indonesia Stock Exchange - Meta Nursita; Karlina, Lilis (Politeknik Raflesia Press, 2024)
This study aims to examine the effect of sales growth, profitability, fixed asset intensity and corporate social responsibility on tax avoidance in property and real estate sub-sector companies on the Indonesia Stock Exchangefor the 2018-2022 period. The research method used in this study was purposive sampling. The sample in this study was 42 companies listed on the Indonesia Stock Exchangefor the 2018-2022 period. Data analysis techniques begin with descriptive statistical tests, then continue with multicollinearity tests, overall model tests, regression model feasibility tests, and hypothesis tests. The statistical method used is panel data regression analysis. The results of the analysis in this study show that partially sales growth does not affect tax avoidance, profitability partially does not affect tax avoidance, fixed asset intensity partially affects tax avoidance and corporate social responsibility does not have a partial effect on tax avoidance and simultaneously sales growth, profitability, fixed asset intensity, and corporate social Responsibility affects tax avoidance.